Faktor Yang Berhubungan Dengan Kepatuhan Minum Obat Pasien TB Di Wilayah Kerja Puskesmas Parongpong - Imanuel Sri Mei Wulandari; Jeanny Rantung; Evelin Malinti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Everyone has a risk of contracting tuberculosis, this disease also develops rapidly in areas that have high humidity. Mycobacterium is infecting through droplets released by the patient. TB treatment is a long-term treatment which medication is consumed every day, to achieve success in treatment requires adherence from patients to consume drugs.Objective: this research is to find out the factors that influence medication adherence of TB patients in Parongpong Health CenterMethod: Methodology of The study used is a quantitative research design with a correlation approach involving 23 respondents who are undergoing treatment at the Parongpong Community Health Center, respondents selected using purposive sampling. The instrument in this study was a questionnaire that was analyzed using the Spearman rho.Result: From the results of data analysis, it was found that gender had a significant relationship with medication adherence. The four factors studied have a significant relationship to medication adherence with p values <0.05, closeness of knowledge relations (0.620), self-stigma (0.467), self-efficacy (0.494), and family support (0.482)).Conclution: Respondents' knowledge is the most dominant factor in influencing medication adherence. Researcher given advice is to maintain adherence to take medication until the completion of the treatment program, to increase the cure rate of TB patients